Socio-economic status, ethnicity and geographical variations in acceptance rates for renal replacement therapy in England and Wales: an ecological study. Issue 6 (23rd October 2009) - Udayaraj, Udaya P; Ben-Shlomo, Yoav; Roderick, Paul; Casula, Anna; Ansell, David; Tomson, Charles R V; Caskey, Fergus J
Abstract : Background: It is not known to what extent the reported regional variations in renal replacement therapy (RRT) acceptance rates in England and Wales are due to differences in the socio-demographic characteristics of the population. Methods: The authors calculated age–gender indirectly standardised RRT rates in 2007 for Primary Care Trusts (PCT)/Local Health Boards (LHB) in England and Wales and Government Office Regions (GOR) in England. Multivariable Poisson regression was used to examine the regional variations in the age–gender standardised RRT rates before and after adjustment for area deprivation (Townsend index) and the proportion of non-white people living in an area. Results: Increasing deprivation of PCT/LHB was associated with higher RRT acceptance rates. RRT rates were higher in PCTs with a greater proportion of non-white people in England (correlation coefficient 0.60, p<0.001) but not in Wales. There were variations in the age–gender standardised RRT rates between PCT/LHBs in England and Wales. Adjusting for deprivation and the proportion of non-white people attenuated the high RRT rate ratio observed in London and West Midlands, but the RRT acceptance rate ratio (95% CI) remained higher in Wales 1.38 (1.22 to 1.57) and lower in North West England 0.82 (0.74 to 0.93) and Yorkshire and Humberside 0.86 (0.77 to 0.98). Conclusions: This study highlights that RRT acceptance rates are positively associated with social deprivation and the proportion of non-white people in a PCT/LHB, but regional variations in RRT acceptance rates still persist despite taking these into account. Further study is required to understand the extent to which these differences reflect variation in underlying need or provision of care.